Coffins and Closets: Vampirism as a Metaphor for Homosexuality in Anne Rice's Interview with the Vampire - Eskelinen, Lotta (My University, 2025)
Metaphors are used as tools to allow an in-depth analysis of literary material. In this thesis I focus on themes of queerness in Anne Rice’s Interview with the Vampire (1976) and study the novel’s portrayal of vampirism and how it metaphorically connects to the lived experience of gay males in real life. I establish the vampiric traits depicted in the novel and how these traits are reflected in both a gay man’s perception of himself and the society’s more stereotypical perception of a homosexual man. This thesis includes discussion of internalized homophobia and religious guilt seen through the lens of vampirism, and offers an alternative perspective to themes of pedophilia present in the novel with a suggestion that the portrayal of youth is instead a commentary on gay beauty standards and ageism in the gay community. My findings show the similarities between Rice’s vampires and homosexuality, providing insight as to why literary vampires have been seen as queer coded since the early days of horror literature and why the queer community often identifies with these marginalized outsiders.
Keywords: queer theory, metaphors, vampires, homosexuality, Anne Rice